1999
DOI: 10.1902/jop.1999.70.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes Mellitus and Oral Health: Assessment of Periodontal Disease

Abstract: Management and prevention of extensive periodontal disease for Type 1 diabetic patients should include strong recommendations to discontinue cigarette smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 30 publications
(28 reference statements)
5
65
0
8
Order By: Relevance
“…They estimated greater bone loss in patients above the age of 55 years and found the older age to be significantly associated with severity of periodontal disease [15][16][17] . Some studies indicated that patient's aging may have more impact on the development of periodontitis than the state of DM (ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They estimated greater bone loss in patients above the age of 55 years and found the older age to be significantly associated with severity of periodontal disease [15][16][17] . Some studies indicated that patient's aging may have more impact on the development of periodontitis than the state of DM (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In one study tooth loss was reported to be associated with extensive periodontal disease as well as with prolonged duration of DM (ref. 16 ). In the present study, the duration of DM appeared to be a predictive factor for the development of severe periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many theories which propose factors such as advanced glycation end products, changes in collagen statue, and altered immune function that causes impaired polymorphonuclear leukocyte function which may facilitate bacterial persistence in the tissue and the accumulation of advanced glycation end products, which results from prolonged and chronic hyperglycaemia and increased secretion of pro-inflammatory cytokines such as tumour necrosis factor-α and prostaglandin 31,32 . The increase in collagenase activity together with the reduction in collagen synthesis will adversely influence collagen metabolism.…”
Section: Diabetes Mellitus and Periodontitismentioning
confidence: 99%
“…A long duration of diabetes is a risk for periodontal diseases (Ainamo & Ainamo 1996, The American Academy of Periodontology 1996), and an association between the duration of diabetes and attachment loss has been found (Firatli et al 1996, Moore et al 1999). Contrary to this, no significant relation between the duration of diabetes and periodontal status has been found by Bridges et al (1996).…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…There is more attachment loss among adult IDDM subjects with poor metabolic balance and/or multiple complications, and in these patients probed pocket depth ≥ 4 mm re-occurs faster after periodontal therapy (Tervonen & Karjalainen 1997). Further, periodontal disease associates with retinopathy (Rosenthal et al 1988, Karjalainen et al 1994, renal disease and cardiovascular complications (Thorstensson et al 1996) as well as neuropathy (Rosenthal 1988, Moore et al 1999.…”
Section: Periodontal Diseasesmentioning
confidence: 99%